Optical Coherence Tomography and Management of a Retinal Granuloma in Presumed Ocular Sarcoidosis. (3rd October 2019) - McMahon, Jeffrey F.; Adam, Murtaza K.; Dunn, James P.
ABSTRACT: Purpose : To highlight the utility of EDI-OCT and periocular steroid administration for the treatment of a retinal granuloma due to presumed ocular sarcoidosis. Methods : Retrospective case-study of a single patient. Results : A 45-year-old African-American male with blurred vision in the right eye was found to have a macula-involving retinal granuloma. Laboratory, imaging, and clinical findings were consistent with a diagnosis of presumed ocular sarcoidosis. Optical coherence tomography (OCT) and fundus photographs were used to document granuloma evolution. Oral prednisone 60mg was initiated and tapered to 10mg within 2 months. Due to systemic side-effects and inadequate treatment response with prednisone, 5 sub-Tenon's triamcinolone acetonide (PSTA) injections were then administered over 7 months, and oral prednisone was discontinued at 6 months. Conclusion : This case demonstrated marked granuloma regression occurring with improvement in visual acuity, highlighting the utility of OCT and PSTA in managing retinal sarcoid granulomas.